(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This paper investigates the distinctive aspects of linguo-cultural and linguo-spiritual relations of proverbs and sayings, with a focus on how they evaluate personality in both the English and Uzbek languages. Proverbs and sayings are integral components of every culture, encapsulating the values, norms, and philosophical outlooks of their respective societies. These expressions often serve as a mirror of the people’s worldview, reflecting attitudes toward human behavior, personal traits, and social interactions. By analyzing the similarities and differences in English and Uzbek proverbs and sayings, this study aims to explore how these linguistic forms shape and evaluate personality traits, emphasizing the relationship between language, culture, and spirituality.